The Influence of Information Technology Mastery, Work Motivation, and Emotional Intelligence on Work Readiness of Vocational High School Students in South Sulawesi - Diyah Mifta Nurwahyuningsih; Anas Arfandi; Nurlita Pertiwi (Journal of Educational Sciences, 2026)
Research on vocational high school students’ work readiness has generally examined technical or motivational factors separately. Consequently, limited studies have simultaneously investigated the roles of information technology mastery, work motivation, and emotional intelligence in shaping students’ work readiness, particularly in public vocational high schools in South Sulawesi Province. The study aims to analyze the effects of information technology mastery, work motivation, and emotional intelligence on the work readiness of vocational high school students. This study employed a correlational research design involving 152 students from Building Information Modeling and Construction Housing Engineering programs in vocational high schools. Data were collected through questionnaires and analyzed using simple linear regression and multiple linear regression techniques. The results indicate that: (1) information technology mastery has a positive effect on work readiness with contribution of 45.90%; (2) work motivation has a positive effect on work readiness with contribution of 35.50%; (3) emotional intelligence has a positive effect on work readiness with contribution of 63.40%; and (4) simultaneously, the three variables positively affect work readiness with combined contribution of 74.60%. The study concludes that information technology mastery, work motivation, and emotional intelligence positively influence work readiness, with emotional intelligence being the most dominant variable